A Praça do Ferreira em quatro tempos: paisagismo e modernidade em Fortaleza - Miyasaki, Julia Santos (2020)
The aim of this research is to investigate the landscape transformations that passed through Ferreira Square, Fortaleza (CE), and its dialogue with modernity throughout the twentieth century, from the interventions made in 1902, 1933, 1969 and 1991. The relevance of the object of study is justified both by the symbolic value that the square still has for the city of Fortaleza, and by the fact that this public space is one of the few that expressed the various landscape practices that occurred over the period. Thus, the work seeks to contribute to the studies on the development of landscaping in Fortaleza and to the writing of the history of this important street, already much examined by researchers from other disciplines. The work is structured in some main points, which are interrelated, seeking to establish the basis for understanding the interventions undertaken in the proposed time frame. It starts from the understanding of the economic, political and culturalideological context in which the works took place; followed by the study of the relationship between landscape practices performed in Brazil and the influence of international currents, as well as the understanding of the development of landscaping in Fortaleza and its relationship with the national context. Finally, we continue with the analysis of the works made throughout the twentieth century, emphasizing its role in the production of landscape and images of the city. To this end, the work is supported by the construction of a theoretical framework through literature review and analysis of documentary sources such as iconography, maps, reports, hemerographic collections and projects. The relevance of the study is justified by its contribution to the understanding of the relationship between the development of landscaping in the city and the transformations that passed through Praça do Ferreira, especially in view of the current treatment landscape that has been destined for public spaces in Fortaleza.